Molecular signaling along the anterior–posterior axis of early palate development - Smith, Tara M.; Lozanoff, Scott; Iyyanar, Paul P.; Nazarali, A.J. (Frontiers in Physiology, 2013)
Cleft palate is a common congenital birth defect in humans. In mammals, the palatal tissue can be distinguished into anterior bony hard palate and posterior muscular soft palate that have specialized functions in occlusion, speech or swallowing. Regulation of palate development appears to be the result of distinct signaling and genetic networks in the anterior and posterior regions of the palate. Development and maintenance of expression of these region-specific genes is crucial for normal palate development. Numerous transcription factors and signaling pathways are now recognized as either anterior- (e.g., Msx1, Bmp4, Bmp2, Shh, Spry2, Fgf10, Fgf7, Shox2) or posterior-specific (e.g., Meox2, Tbx22, Barx1). Localized expression and function clearly highlight the importance of regional patterning and differentiation within the palate at the molecular level. Here, we review how these molecular pathways and networks regulate the anterior-posterior patterning and development of secondary palate. We hypothesize that the anterior palate acts as a signaling center in setting up development of the secondary palate.